2008
DOI: 10.1136/thx.2007.085241
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and PDGFR differentially promote growth in malignant epithelioid mesothelioma of short and long term survivors

Abstract: Background: Malignant pleural mesothelioma (MPM) is an asbestos related tumour difficult to detect early and treat effectively. Asbestos causes genetic modifications and cell signalling events that favour the resistance of MPM to apoptosis and chemotherapy. Only a small number of patients, approximately 10%, survive more than 3 years. The aim of our study was to assess possible differences within signalling pathways between short term survivors (survival ,3 years; STS) and long term survivors (survival .3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…Normal mesothelial cells express PDGFR-α while mesothelioma tumors express both PDGF-AA and PDGF-BB ligands as well as PDGFR-α and PDGFR-β (86)(87)(88). While the staining pattern of PDGFR-β immunoreactivity in frozen sections of MPM are consistent with MPM tumor cell expression of PDGFR-β, the function of PDGFR-β within tumor cells, as opposed to the associated stroma, has not been well described.…”
Section: Pdgfr Inhibitorsmentioning
confidence: 58%
“…Normal mesothelial cells express PDGFR-α while mesothelioma tumors express both PDGF-AA and PDGF-BB ligands as well as PDGFR-α and PDGFR-β (86)(87)(88). While the staining pattern of PDGFR-β immunoreactivity in frozen sections of MPM are consistent with MPM tumor cell expression of PDGFR-β, the function of PDGFR-β within tumor cells, as opposed to the associated stroma, has not been well described.…”
Section: Pdgfr Inhibitorsmentioning
confidence: 58%
“…The patients were divided into two groups using 36 months as cutoff survival. Twenty-six patients were identified as long survivors (LS; one USA, one UK, one Austria, three France, five Turkey, 15 Italy) and 22 as short survivors (SS; five UK, eight Italy, nine Austria) [27].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent studies showed that adipocytes, circulating multipotential fibrocytes and adult bone marrow-derived stem cells are able to differentiate into both epithelial and mesenchymal cells [61][62][63]. Interestingly, mesothelial cells also have the ability to change phenotype to become smooth muscle cells and fibroblasts in internal organs and their vasculature, so normal mesothelial cells are multipotential, similar to stem cells [64].…”
Section: Figurementioning
confidence: 99%